Charting New Terrain in Work Design: A Study of Hybrid Work Characteristics. Issue 3 (21st October 2018) - Xie, Jia Lin; Elangovan, A.R.; Hu, Jing; Hrabluik, Coreen
Abstract: Research on work design to date has focused on work characteristics associated primarily with one of three domains—task, social, or contextual. The present paper introduces a new concept—hybrid work characteristics—that refer to work characteristics which are not fully captured within any one of the three domains but possess features from more than one domain. We identify boundarylessness, multitasking, non‐work‐related interruptions, and demand for constant learning as hybrid work characteristics in the modern work environment. Furthermore, we theorise that boundarylessness, multitasking, and demand for constant learning carry both enriching and depleting potential, but non‐work‐related interruptions have only depleting potential. In our study, we developed instruments to assess the four work characteristics and tested their relationship with jobholders' job satisfaction, occupational commitment, emotional exhaustion, and somatic health symptoms, through three independent studies (a total of 968 employees across a wide range of jobs). The results demonstrated convergent, predictive, and discriminant validity for the newly developed scales, and showed partial support for the prediction that boundarylessness and multitasking are beneficial as well as detrimental for jobholders and consistent support for the depleting potential inherent in non‐work‐related interruptions. We conclude with a discussion of how our exploration of hybrid work characteristics contributes to research on work design and management practices.